2021
DOI: 10.1097/mca.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and infarct size, microvascular obstruction, left ventricular function and clinical outcomes after ST-segment elevation myocardial infarction

Abstract: Participating studies, inclusion criteria and definitionsAs previously described [15], the present study represents an academic collaboration between the principal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(63 reference statements)
0
5
0
Order By: Relevance
“… 95 Furthermore, cold spells during pregnancy have been linked to increased incidence of congenital artic coarctation, 96 while temperature extremes may be associated with increased symptoms of hypertrophic cardiomyopathy 97 and with lower left ventricular ejection fraction after myocardial infarction. 98 All of these conditions are recognized causes 99 , 100 of Group 2 PH.…”
Section: Direct and Indirect Impact Of Climate Change On Pvdmentioning
confidence: 99%
See 2 more Smart Citations
“… 95 Furthermore, cold spells during pregnancy have been linked to increased incidence of congenital artic coarctation, 96 while temperature extremes may be associated with increased symptoms of hypertrophic cardiomyopathy 97 and with lower left ventricular ejection fraction after myocardial infarction. 98 All of these conditions are recognized causes 99 , 100 of Group 2 PH.…”
Section: Direct and Indirect Impact Of Climate Change On Pvdmentioning
confidence: 99%
“…Air pollution not only increases the incidence of LHD, 47 but preliminary animal studies have found a worsening of PH in a left ventricle failure mouse model (through transverse aortic constriction) when exposed to PM 2.5 , 30,31 and a MESA study found greater left ventricular mass in subjects exposed to higher air pollution 95 . Furthermore, cold spells during pregnancy have been linked to increased incidence of congenital artic coarctation, 96 while temperature extremes may be associated with increased symptoms of hypertrophic cardiomyopathy 97 and with lower left ventricular ejection fraction after myocardial infarction 98 . All of these conditions are recognized causes 99,100 of Group 2 PH.…”
Section: Direct and Indirect Impact Of Climate Change On Pvdmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 Redfors et al showed that extreme temperatures were related to larger infarct size and smaller left ventricular ejection fraction in patients with ST-segment elevation myocardial infarction. 12 Hensel et al reported that even in moderate climatic conditions, low temperatures can still lead to an increased frequency of CAD, especially below 10 °C. 13 A time-series analysis study based on major cities across China found that the mortality risk and burden from main cardiopulmonary diseases was more pronounced in temperate monsoon and subtropical monsoon climatic zones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have shown that improving the utilization of fatty acids and sugars is an effective means to treat heart failure after myocardial infarction. In recent years, scholars from China and other countries have discussed the changes of small molecule metabolite content, aiming to explore the pathogenesis of heart failure and find new therapeutic targets (Redfors et al, 2021). Amino acids play a vital role in human vitality and biosynthesis.…”
Section: Introductionmentioning
confidence: 99%